Impact of land use change and climate on the Brazilian Amazon: a review on carbon stocks and greenhouse gas emissions - Moraes, Lorena Maués (2025)
Historically, land-use changes in the Brazilian Amazon, such as the conversion of forests to pastures, have significantly impacted carbon and nitrogen cycles, contributing to greenhouse gas emissions and potentially compromising environmental sustainability. This review explores the effects of these changes on soil carbon and nitrogen stocks, emphasizing the role of sustainable practices and public policies in mitigating environmental impacts. Findings indicate that, although forest-to-pasture conversion may reduce soil organic carbon stocks by up to 11.3%, practices such as agroforestry systems, sustainable pasture management, and crop-livestock-forestry integration (CLFI) have the potential to reverse these effects by promoting carbon sequestration and soil conservation. Public policies such as the Low Carbon Agriculture Plan (ABC Plan) and the Amazon Fund are highlighted as essential pillars for sustainable development in the region. It is concluded that the adoption of sustainable agricultural practices, integrated with robust environmental policies and technological innovation, can transform the Amazon into a global model of balance between economic development and environmental conservation. Future studies should prioritize integrated assessments of carbon stocks, gas emissions, and socioeconomic indicators to support more effective and regionally adapted public policies.